On Legal Bases and Values Underpinning EU Competence in Sport - Weingerl, Petra (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
Sport occupies a unique position in European society. It is at once a cultural practice, an economic activity, a tool for social integration, and an increasingly globalised industry. Within the EU, this intersection raises complex questions regarding the scope of EU competence and the normative foundations of EU action in the field of sport. This article examines legal bases and values underpinning EU competence in sport through a three-step analytical framework. First, it sketches the constitutional foundations of EU competence in sport, focusing on the principle of conferral and Article 165 of the TFEU. Second, it clarifies what the EU can or could do in sport within the existing Treaty framework, paying particular attention to the role of internal market law and the jurisprudence of the CJEU. Third, it turns to the normative question of what the EU should do in this field, examining the values that could justify a more active European role in regulating sport.